Extended characterization of multi-drug resistant organisms colonising neonates at a tertiary hospital in Johannesburg, South Africa. - Mntla, Nonkululeko Marcia (My University, 2024)
Neonatal deaths remain high globally, particularly in sub-Saharan Africa. A third of deaths are due to infections, often secondary to multi-drug resistant (MDR) organisms. The purpose of this study was to investigate the prevalence of MDR ESKAPE+ C. auris colonisation amongst hospitalised neonates, to determine risk factors associated with MDR colonisation, and perform antimicrobial resistance characterization of these isolates. Two hundred and fifty-eight swabs were collected from 86 hospitalised neonates at a tertiary South African hospital between November and December 2020. A total of 135 ESKAPE+ C. auris isolates were identified; 68% were MDR. Majority of neonates (65%) were colonised with extended spectrum betalactamase (ESBL) producing Klebsiella pneumoniae, followed by extensivelydrug resistant (XDR) Acinetobacter baumannii. New Delhi metallo-beta-lactamase (NDM) producing A. baumannii were more prevalent than carbapenemase producing Enterobacterales (CPE). A prolonged hospital stay, median=14 days (p<.001) was identified as a risk factor for MDR organism colonisation. The high prevalence of MDR ESKAPE+ C. auris colonisation supports use of non-invasive samples to determine colonisation prevalence. More data are needed to develop improved surveillance systems which should incorporate colonisation swabs and clinical biomarkers in neonates with independently established risk factors.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Microbiological Pathology to the Faculty of Health Sciences, University of the Witwatersrand, School of Pathology, Johannesburg, 2023
Keywords: Multi-drug resistant; Neonatal deaths; SDG-3: Good health and well-being; SDG-16: Peace, justice and strong institutions